Abdominal skin metastasis in endometrial cancer - Eccita Rahestyningtyas; Pungky Mulawardhana; Tomy Lesmana (Majalah Obstetri dan Ginekologi, 2019)
Objectives: Surgical wound metastases in stage 1 endometrial cancer are possible, with a variety of different pathophysiological possibilities. Comprehensive management is needed to keep the patient on the possibility of a good prognosis.Cases Report: During January 2015 – January 2018 at dr. Soetomo Hospital, there were 2 cases of metastatic endometrial cancer in the laparotomy wounds by which the condition is very rare. Case 1, The patient was diagnosed with endometrial carcinoma following the results of curettage. Anatomical pathology examination was done and obtained grade 2 endometrioid adenocarcinoma. In Case 2, the patient underwent Total Abdominal Hysterectomy and Bilateral Salpingo-Oophorectomy in 2013 at Mojokerto General Hospital, indicating Uterine Fibroids and Ovarian Cysts. The results of anatomical pathology examination were unknown. On April 2017, the patient complained abdominal swelling since 3 months ago.Conclusion: In January 2015 - January 2018, 2 cases of metastatic endometrial cancer was found in a former laparotomy operation where this condition is very rare in endometrial cancer cases with low grade ,so that follow-up, monitoring and more vigilance are required in patients with low-grade endometrial Ca who have finished undergoing a surgery and chemotherapy. Rapture or mass resection, followed by external radiation, may be performed in patients with recurrence in the laparotomy wound area or in patients with high risk factors for endometrial cancer such as a history of estrogen use, tamoxifen, nullipara, obesity, diabetes mellitus, and family history of endometrial cancer. Currently, there is no fixed procedure (guideline) in RS. Dr. Soetomo to overcome recurrences especially in the scars of cancer surgery.